Molecular Cloning and Characterization of Babesia orientalis Rhoptry Neck 2 BoRON2 Protein - Ngabu Malobi; Lan He; Long Yu; Pei He; Junwei He; Yali Sun; Yuan Huang; Junlong Zhao (Journal of Parasitology Research)
Babesiosis caused by Babesia orientalis is one of the most prevalent infections of water buffalo transmitted by Rhipicephalus haemaphysaloides causing a parasitic and hemolytic disease. The organelles proteins localized in apical membrane especially rhoptries neck and microneme protein form a complex called moving junction important during invasion process of parasites belonging to apicomplexan group, including Babesia species. A truncated fragment coding a 936 bps fragment was cloned in pMD-19T and subcloned into pET32 (a)+ expression vector, expressed in E. coli BL21. Purified recombinant BoRON2 was used to produce polyclonal antibody against BoRON2. Here, we identified the full sequence of gene encoding the rhoptry neck 2 protein that we named BoRON2 which is 4035 bp in full-length open reading frame without introns, encoding a polypeptide of 1345 amino acids. Western blot of rBoRON2 probed with buffalo positive serum analysis revealed a band of around 150 kDa in parasite lysates, suggesting an active involvement during invasion process. These findings most likely are constructive in perspective of ongoing research focused particularly on water buffalo babesiosis prevention and therapeutics and globally provide new information for genes comparative analysis.